Navigating Uncertainty in Sustainability Assurance: Challenges of the Corporate Sustainability Reporting Directive in Romania and Austria - Julia Baldauf; Cristina Circa; Alin-Constantin Dumitrescu; Sabine Graschitz (Amfiteatru Economic)
The implementation of the Corporate Sustainability Reporting Directive (CSRD), which requires assurance on sustainability reports for numerous companies, has reached different implementation stages throughout the EU. This study investigated the key uncertainties and challenges arising from the new assurance obligations, focusing on auditors in Romania and Austria. We explored auditors' perceptions of legal uncertainties, the integration of financial and sustainability reporting, and the need for additional resources and competencies, by means of a questionnaire-based survey. The results indicated that auditors that had already provided sustainability assurance were better informed about CSRD implementation, with significant differences in their perception of specific matters. Country-specific variations were identified, to a small extent. Legal uncertainties and the need for technical expertise were highlighted as major challenges. The study provides valuable insights into the current state of sustainability assurance in the context of the CSRD, and contributes to the literature by includin g perspectives from both Big4 and Non-Big4 audit firms.